PENGEMBANGAN LKPD BERBASIS GENERATIF UNTUK MATERI RELASI DAN FUNGSI KELAS VIII SMP/MTS - Syilvia Wulandari (Jurnal Edukasi dan Penelitian Matematika, 2020)
This researchaaimsatoadevelopamathematical learningatoolsainatheaformaof generative-based student worksheets (LKPD) for relationship materials and grade VIII SMP/MTS functions. The quality of the developed device is assessed based on aspects of validity and practicality. Thisadevelopmentaresearchauses plompamodelaconsistingaof three stages, namelyapreliminaryaresearch phase, developmentaor prhotyping phase, and assessmentaphase. iInsthesinitialsinvestigationwphase,wneedswanalysis,wcurriculumwanalysis,conceptwanalysisw and analysiswofwstudents. The prototype phase isacarriedwout inwthe activity of designing learningwdevices consisting of prototype 1, and prototype 2. In prototype 1 is conducted self evaluation and expert reviews. Expert reviews are conducted to see the validity of the learning tools developed. In prototype 2, one-to-one evaluation was conducted by testing validated LKPD to three students with different cognitive abilities. Furthermore, the assessment phase to see the practicality of LKPD through the results of practical questionnaires on the response of educators and students. Thewresultssofwstudy show thatwthe developmenwtof generativewbased LKPD for relationship materials and grade VIII functions of SMP/MTS is categorized as valid and practical. Judging by the results of the analysis of validity data in terms of content feasibility, components in LKPD, language, and learning activities have a validity level with a scale of 3.54 categorized very valid. In addition, LKPD also meets the practical criteria of the results of the response questionnaire of students with a scale of 3.40 categorized very practical.  Keywords— Design research, students worksheet, generative model, relation and fungtion